SME Owners’ Willingness to Adopt Renewable Energy Technologies for Socio-Economic Development: A Perspective for Policy Decision Makers - Ahmed, Khalil; Shah, Asif Ali; Bhutto, Arabella; Sahito, Zahid Hussain (Pakistan Journal of Humanities and Social Sciences, 2024)
This study investigates the willingness of small and medium enterprise (SME) owners and farmers in the rural Khairpur district of Sindh, Pakistan, to adopt clean energy initiatives (CEIs) in the agricultural sector. The research applies the Theory of Planned Behavior (TPB) to evaluate eight hypotheses related to attitudes, subjective norms, and perceived behavioural control (PBC) factors influencing the adoption of CEIs. Data was collected from 108 participants, and IBM SPSS was used for analysis. Key factors such as production quality, seasonal expenses, peer influence, market demand, and switching costs were examined. The results indicate that attitudes toward CEIs, such as improved production quality, lower seasonal expenses, and peer influence, positively impact the willingness to adopt CEIs. However, government policies and the diffusion of technologies were found to have an insignificant effect. The study concludes with policy recommendations aimed at facilitating the broader adoption of CEIs in agriculture to promote socio-economic development.